Pengaruh Kepemimpinan Dan Kepuasan Kerja Terhadap Disiplin Kerja Dengan Motivasi Kerja Sebagai Variabel Mediasi: Di Biro Umum Dan Administrasi Pimpinan Sekretariat Daerah Provinsi Papua - Dosinaeng, Rafael B. D. R.; Kambuaya, Balthasar; Tuhumena, Ruben (Magister Manajemen Universitas Cenderawasih, 2025)
This study aims to analyze the influence of leadership and job satisfaction on employee work discipline, mediated by work motivation, as well as examine the relationships among these variables. This research employs a quantitative method with a population consisting of employees working in the Bureau of General Affairs and Leadership Administration of Papua Province. The sample consists of 158 employees selected using the simple random sampling technique. Data collection methods include observation, literature review, and questionnaire distribution. Data analysis is conducted using path analysis with the aid of SPSS version 3.0 software. The results indicate that leadership has a significant influence on work motivation, whereas job satisfaction does not significantly affect work motivation. Furthermore, work motivation has a significant impact on work discipline. Leadership also significantly affects work discipline through work motivation, while job satisfaction does not significantly influence work discipline through work motivation.